Hemodynamic Response to Glucose-Insulin Infusion and Meals during Hemodialysis - Christoffer Svinth-Johansen; Mark Reinhard; Per Ivarsen (Karger Publishers, 2020)
Introduction: Intradialytic nutrition may improve nutritional status and reduce mortality in patients on maintenance hemodialysis (HD) but has been associated with adverse events, mainly hemodynamic instability. Some dialysis centers therefore restrict intradialytic meals. In 2 clinical studies, we investigated the effects of intradialytic glucose-insulin infusion (GII) and meal intake on blood pressure (BP), pulse wave velocity (PWV), pulse wave analysis (PWA), and cardiac output (CO). PWA yielded augmentation index standardized with heart rate 75 (AIx@HR75). Methods: In the GII study, 12 nondiabetic HD patients had BP, PWV, PWA, and CO measured during 3 HD sessions: standard HD, HD with glucose infusion, and HD with GII. In the Meal study, 12 nondiabetic patients had BP and PWA measured on 3 study days: meal alone (non-HD), meal and HD, 2 meals and HD. Twelve matched healthy controls completed the non-HD day. Findings: In the GII study, glucose or GII had no additional effects on hemodynamic parameters compared with standard HD. HD resulted in a decrease in systolic BP of 13%, in diastolic BP of 9%, in AIx@HR75 of 17%, and CO of 18%. PWV was reduced by only 5%. In the Meal study, a meal alone did not change BP, whereas the combined influence of HD and meal intake reduced systolic BP with 22% and diastolic BP with 19%. Furthermore, AIx@HR75 decreased by 37% on HD days and by 36% in controls, but was unaffected on non-HD days. Discussion: In the GII study, HD significantly reduced BP, AIx@75, and CO, whereas PWV remained almost constant. No additional effects were observed by concomitant GII during HD. BP reductions seemed larger in the Meal study compared with the GII study. Taken together, HD per se appears as the main discriminant for intradialytic hypotension but in hemodynamically unstable patients the timing and route of nutrition provision should be considered carefully.